Experimental Research on the Impact of Ion Exchange and Infiltration on the Microstructure of Rare Earth Orebody - Xiaojun Wang; Yulong Zhuo; Shuqiang Deng; Yongxin Li; Wen Zhong; Kui Zhao (Advances in Materials Science and Engineering)
To detect the evolutional characteristics of pore structure in ore leaching process of ion-type rare earth, this paper analyzes the influence mechanism of ion exchange seepage action on the microstructure of orebody, and an experiment for remodeling rare earth saturated samples and ore leaching was designed. Using nuclear magnetic resonance technology obtains the pore structure T2 map of H2O and (NH4)2SO4 solution in the ore leaching process and inverts and reconstitutes the pore structure distribution image. The results of contrastive analysis experiments indicate that impact factors of the ore leaching process on the microstructure of rare earth orebodies include two aspects: solution seepage and ion exchange. The main factor of pore structure distribution is the ion exchange action, determined by a dual effect. The sole action of solution seepage leads to an increase in pore size, which means that pore size structure is changing from small and medium to macro. Ion exchange gives rise to the movement and restructuring of particles, which results in a decrease in pore sizes. The pore structure changes from loose to compact; in the entire ore leaching process, the ion exchange action advances in a layered shape along the direction of seepage, and the chemical replacement and physical seepage alternately impact the microstructure of the orebodies.